(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The aim of present study was to summaries the literature on medicinal plants prepared by survey on indigenous knowledge of tribes of Rajasthan on traditional medicinal plants used by them for improving their sexual performance and problem associated with sexuality.